Beak trimming handbook for egg producers : best practice for minimising cannibalism in poultry - Glatz, P. C.; Bourke, Michael (Land Links, 2006)
"This book is a straightforward, practical guide for egg producers on beak trimming. It explains why, how and when birds are beak trimmed, production responses of birds to trimming and alternatives to beak trimming."--Resumé vydavatele
Terminologický slovník
Keywords: drůbež; kanibalismus; poultry; cannibalism; příručky; elektronické knihy; handbooks and manuals; electronic books